THE ESTIMATION OF CARCASS WEIGHT AND CARCASS PERCENTAGE BASED ON BODY WEIGHT OF MALE KACANG GOAT IN VARIOUS AGE AT SUKUN ABATTOIR OF MALANG - Al Isa, Riski Yusuf (Jurnal Sains Peternakan, 2015)
The purpose of this study was to determine the prediction of carcass weight and carcass percentage by body weight goat. Methods of data analysis using simple linear regression and correlation coefficients least Square simple linear. From the research, the average weight of each kacang age male goat as follows PI1 = 16.41 ± 2.02: PI2 = 17.92 ± 1.82: PI3 = 20.35 ± 2.56: PI4 = 24.82 ± 4.20. While the regression equation between body weight with kacang male goat carcass weight PI1 y = 0.92 + 0.47: PI2 y = 0.20 + 0.45: PI3 y = 0.95 + 0.49: PI4 y = 1.23 + 0.51. while the regression equation between body weight with kacang male goat carcass percentage PI1  y = 36.59 + 0.31: PI2  y = 43.31 + 0.06: PI3 y = 40.33 + 0.22: PI4 y = 41.33 + 0.19. The regression equation above results indicate the existence of a positive relationship is highly significant (t  > t table 0.01)By looking at the regression equation it can be concluded that the percentage of carcass and  weight can be estimated based on the weight of goat pieces, each increase of 1 kg body weight will be followed by an increase in carcass weight and carcass percentage. Carcass weight and carcass percentage can be estimated based on the weight of intersection, every body weight increase will be followed by an increase in carcass weight and carcass percentage. It is recommended that the weighing of livestock, to obtain estimates of carcass weight and percentage by weight of intersection.Keywords : Carcass weight, Carcass percentage, Cut weight, Various ages